Collective pause: improving staff performance in acute medicine through a brief mindfulness‐based group programme. Issue 8 (31st May 2022) - Kang, Matthew; Gibbs, Harry; Selzer, Rob; Hudaib, Abdul‐Rahman; Aung, Ar Kar; Gibbs, Jo
Abstract: Background: Hospital wards are a complex and dynamic environment that rely on optimal staff performance. However, there is little research evaluating group interventions to improve staff attention and teamwork. Aims: To evaluate whether a regular, short and guided group mindfulness practice for staff in an acute general medicine team improves attention and teamwork. Methods: A 10‐min programme comprising mindfulness exercises and techniques was delivered daily to a multidisciplinary general medicine team based in a tertiary hospital for 4 weeks. This was undertaken immediately prior to the team's interdisciplinary ward round. We used a mixed‐method design, with self‐rated surveys to measure mindfulness and staff perception of hospital safety culture, and a focus group to understand participants' experiences. We estimated mean differences using Kruskal–Wallis tests across 10 time‐points and thematically analysed recorded transcripts. Results: There was an increase in staff attention to the team meeting as measured by the decentering domain across time ( P < 0.001). There was a trend to greater staff openness with a non‐significant increase in curiosity ( P = 0.14). We identified two overarching qualitative themes: feasibility of the programme and impact on staff and workplace. The programme was a calming circuit breaker to staff's day, which aided in feeling more connected to the group and subjectively better ward round experience. The logistics of the programme, including timing, and the facilitator developing trust with the participants, appear important in implementation. Conclusion: A brief mindfulness‐based intervention delivered to a general medical team improves staff attention at a multidisciplinary team meeting and team functioning.